Anammox bacteria in different compartments of recirculating aquaculture systems. (21st November 2011) - van Kessel, Maartje A.H.J.; Harhangi, Harry R.; Flik, Gert; Jetten, Mike S.M.; Klaren, Peter H.M.; Op den Camp, Huub J.M.
Abstract : Strict environmental restrictions force the aquaculture industry to guarantee optimal water quality for fish production in a sustainable manner. The implementation of anammox (anaerobic ammonium oxidation) in biofilters would result in the conversion of both ammonium and nitrite (both toxic to aquatic animals) into harmless dinitrogen gas. Both marine and freshwater aquaculture systems contain populations of anammox bacteria. These bacteria are also present in the faeces of freshwater and marine fish. Interestingly, a new planctomycete species appears to be present in these recirculation systems too. Further exploitation of anammox bacteria in different compartments of aquaculture systems can lead to a more environmentally friendly aquaculture practice.